2012
DOI: 10.1016/j.bone.2011.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow fat has brown adipose tissue characteristics, which are attenuated with aging and diabetes

Abstract: Fat occupies a significant portion of bone cavity however its function is largely unknown. Marrow fat expands during aging and in conditions which affect energy metabolism, indicating that fat in bone is under similar regulatory mechanisms as other fat depots. On the other hand, its location may determine specific functions in the maintenance of the environment for bone remodeling and hematopoiesis. We have demonstrated that marrow fat has a distinctive phenotype, which resembles both, white and brown adipose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
242
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 237 publications
(256 citation statements)
references
References 43 publications
12
242
2
Order By: Relevance
“…36,37 Recently, it was shown that MAT has a distinct phenotype resembling both WAT and BAT. 38 The authors showed that MAT expresses several BAT-selective genes including Prdm16, Dio2 and Pgc1α at similar levels as in the interscapular BAT depot. However, the expression level of the thermogenic effector gene Ucp1 was very low, possibly due to the presence of unstimulated beige or beige-like adipocytes in the MAT.…”
Section: Bat and Thermogenic Adipocytesmentioning
confidence: 99%
“…36,37 Recently, it was shown that MAT has a distinct phenotype resembling both WAT and BAT. 38 The authors showed that MAT expresses several BAT-selective genes including Prdm16, Dio2 and Pgc1α at similar levels as in the interscapular BAT depot. However, the expression level of the thermogenic effector gene Ucp1 was very low, possibly due to the presence of unstimulated beige or beige-like adipocytes in the MAT.…”
Section: Bat and Thermogenic Adipocytesmentioning
confidence: 99%
“…Nishio et al (2012) developed an alternative approach to reprogram hES and IPS cells into functional brown adipocytes both in vitro and in vivo with an efficiency of O90% without utilizing exogenous gene transfer. The protocol was initially discovered by observations that conditions which were established to differentiate cells of the haematopoietic lineage resulted in the production of significant numbers of brown adipocytes (Thorns et al 2008, Krings et al 2012. They employed a haemopoietic cocktail (HC) composed of KIT ligand (KITGL), fms-related tyrosine kinase 3 ligand (FLT3LG), interleukin 6 (IL6), and VEGF along with the previously reported BAT inducer BMP7 (Tseng et al 2008).…”
Section: Brown Adipocytes Differentiated From Hes and Ips Cellsmentioning
confidence: 99%
“…Later, these cells have been proposed to have a role as an energy source, or as modulators of adjacent tissue by the production of paracrine, and autocrine factors (reviewed in Rosen et al, 2009). In fact, adipokines, steroids, and cytokines (Lee et al, 2002;Pino et al, 2010;Rosen et al, 2009;) can exert profound eff ects on neighboring marrow cells, sustaining or suppressing hematopoietic and osteogenic processes (Omatsu et al, 2010;Krings et al, 2012;Rosen et al, 2009;Rodríguez et al, 2008). Thus, the function of bone marrow adipose tissue may be similar to that of extra medullary fat.…”
Section: Relationship Between the Osteo-/ Adipogenesis Pro-cesses -Thmentioning
confidence: 99%